Quilombo de Batoque: memórias de resistências Afropindorâmicas - Cordeiro, Joseli do Nascimento (2024)
The existence of quilombos for a long time was described in History as something referring to the past, characterized by a colonialist vision as a place of escape from slavery. Denying and making the protagonism of the people who form it impossible. Ignoring their way of life and sovereign knowledge. In order to construct a narrative against colonization that aims to think about quilombos beyond the way described above, this research proposes to discuss the memories and processes of resistance of the quilombola community of Batoque, located in the municipality of Pacujá, in the interior of the State. from Ceará. The community is currently made up of 99 families, most of whom practice agriculture, and according to the oldest, it has been in existence for over 250 years. This work, entitled Quilombo de Batoque: Memories of Afropindorâmic Resistances, aims to discuss and problematize the resistance of this community. The term resistance is understood here in its broadest sense, from the analysis of the narratives that tell about its formation; the memories about a past that becomes present every day; actions that seek to continue their way of life and maintain the connection with their ancestry; the daily struggles to stay and protect the territory; of the sovereignty of knowledge that was passed on and often covered up or given new meanings as a strategic way so that it would not be lost. In this way, the present work aims to analyze the relationships between memory, narratives and the articulations of meaning of the Batoque quilombo in the exercise of its sovereignty. For this purpose, we used in our body of sources, dialogues with the quilombolas of Batoque, Images provided by the association and bibliography relevant to the topic.